2009
DOI: 10.1371/journal.pone.0006005
|View full text |Cite
|
Sign up to set email alerts
|

Cell Therapy Attenuates Cardiac Dysfunction Post Myocardial Infarction: Effect of Timing, Routes of Injection and a Fibrin Scaffold

Abstract: BackgroundCell therapy approaches for biologic cardiac repair hold great promises, although basic fundamental issues remain poorly understood. In the present study we examined the effects of timing and routes of administration of bone marrow cells (BMC) post-myocardial infarction (MI) and the efficacy of an injectable biopolymer scaffold to improve cardiac cell retention and function.Methodology/Principal Findings 99mTc-labeled BMC (6×106 cells) were injected by 4 different routes in adult rats: intravenous (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 45 publications
8
69
0
5
Order By: Relevance
“…Rat adiposederived stem cells (rASCs) were isolated, characterized, and maintained in culture as previously described [22,23].…”
Section: Cell Isolation Ex Vivo Expansion and Asc Characterizationmentioning
confidence: 99%
“…Rat adiposederived stem cells (rASCs) were isolated, characterized, and maintained in culture as previously described [22,23].…”
Section: Cell Isolation Ex Vivo Expansion and Asc Characterizationmentioning
confidence: 99%
“…17,20 Previous studies have also demonstrated that fibrin glue could improve the survival of injectable skeletal myoblasts, bone marrow cells, marrowderived cardiac stem cells, adipose-derived stem cells, and human induced pluripotent stem cell-derived cardiomyocytesin MI hearts. [21][22][23][24][25][26] Furthermore, injection of fibrin alone (without cells) could preserve cardiac function after MI and prevent negative LV remodeling. 27 Also, our previous report has demonstrated the positive role of platelet fibrin gel in cardiac repair after MI.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the optimal timing for cell therapy, the route of administration is also of importance to receive the best efficacy of transplanted cells [13]. In the setting of heart failure, cardiopoietic and mesenchymal stem cells were delivered by endomyocardial injections guided by left ventricular electromechanical mapping [11,14].…”
Section: Discussionmentioning
confidence: 99%